2012
DOI: 10.3233/wor-2012-0773-4838
|View full text |Cite
|
Sign up to set email alerts
|

Need for recovery assessment among nursing professionals and call center operators

Abstract: The present study descriptively compares the need for recovery (NFR) among 128 nursing professionals (nurses) and 223 call center operators according cutoff points in the literature (45 and 50) and by means of statistical tests, and verifies the association between NFR scores and the presence of musculoskeletal symptoms. NFR was evaluated with the Need for Recovery Scale and musculoskeletal symptoms were evaluated with the Nordic Musculoskeletal Questionnaire. At a 45 point cutoff, 22% of the call-center worke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
0
5
0
3
Order By: Relevance
“…The Need For Recovery (NfR) scale is an eleven-item scale including items like: ‘I find it difficult to relax at the end of working day’ or ‘In general, it takes me over an hour to feel fully recovered after work’ [ 31 ]. Multiple studies have confirmed the quality and validity of this scale for evaluating work-related need for recovery [ 31 , 33 , 44 , 45 ]. The NfR scale will be used in the current study to evaluate need for recovery experienced in daily-life.…”
Section: Introductionmentioning
confidence: 98%
“…The Need For Recovery (NfR) scale is an eleven-item scale including items like: ‘I find it difficult to relax at the end of working day’ or ‘In general, it takes me over an hour to feel fully recovered after work’ [ 31 ]. Multiple studies have confirmed the quality and validity of this scale for evaluating work-related need for recovery [ 31 , 33 , 44 , 45 ]. The NfR scale will be used in the current study to evaluate need for recovery experienced in daily-life.…”
Section: Introductionmentioning
confidence: 98%
“…Work-induced fatigue has an important role in the etiology of psychophysical overloads (5) . Recently, studies have adopted measures of fatigue in the nursing context (3,(6)(7) . This variable has demonstrated a high prevalence and an association with deleterious working conditions (6,(8)(9) .…”
Section: Introductionmentioning
confidence: 99%
“…Occupational risk factors associated to nursing professionals' activity may be related specifically to the complexity of care, double shifts, physical and mental work overloads and overtime (12) . Multidimensional measures such as fatigue are key in the context of nursing activity, because they can help to detect situations inducing cumulative loads and avoid long-term effects (7) . In addition, the traditionally used analysis of work ability and musculoskeletal discomfort is a useful tool to evaluate health status and plan preventive actions.…”
Section: Introductionmentioning
confidence: 99%
“…A Escala de Necessidade de Descanso (ENEDE) é uma versão traduzida para a língua portuguesa e adaptada para cultura brasileira a partir da versão inglesa da Need for Recovery Scale (Moriguchi et al, 2010). O questionário, identificado em três textos (Patterson et al, 2014;Moriguchi et al, 2012;Croon, Sluiter & Frings-Dresen, 2006), tem por finalidade mensurar a necessidade de descanso após um dia de trabalho e, assim, proporcionar a avaliação da fadiga induzida e a qualidade do tempo de recuperação. A ENEDE também avalia os efeitos da fadiga em curto prazo: falta de atenção, irritabilidade, isolamento social, redução do desempenho e da qualidade do tempo de recuperação após o trabalho.…”
Section: Metodologiaunclassified